Factors related to abnormal neuroimaging in children with first unprovoked seizure - TAVASSOLI, Azita; NOORMOHAMADI, Shahriar (Iranian Journal of Child Neurology, 2011)
Objective The first attack of unprovoked seizure is more frequent than recurrent one and neuroimaging is one of the main parts of the evaluation of these attacks in order to demonstrate the cause and predict the prognosis. The aim of this study was to determine the incidence of abnormal neuroimaging and related factors in children with the first unprovoked seizure. Materials & Methods A 7-year retrospective chart review was done on all children who were visited at Ali-Asghar Children’s Hospital with the first unprovoked seizure and underwent neuroimaging including brain computed tomography or magnetic resonance imaging. The diagnostic criteria for the first unprovoked seizure in this study were based on the absence of any immediate or acute cause for the first seizure such as fever, head trauma, hypoglycemia, hypocalcemia, electrolyte imbalance and etc. We compared the rate of abnormal neuroimaging in patients according to different clinical and electroencephalographic (EEG) parameters. Results One hundred and forty two patients (63 females, 79 males) were included in the study. Twenty eight patients (20%) had abnormal neuroimaging. CT scan and MRI were done in 63% and 37% of the patients, respectively. The most common abnormalities were cerebral dysgenesis (n=9) and cortical brain atrophy (n=6). Patients who were abnormal on neurologic examination had a higher rate of abnormal imaging in comparison with neurologically normal children (51% vs. 10%) (p<0.05). Abnormal imaging was more frequent in children with an epileptiform activity in EEG compared to normal EEG (34% vs. 11%) (p=0.01). Although not statistically significant, partial type of seizure, seizure recurrence within 24-hr and age 3-12 year were also associated with a higher rate of abnormal neuroimaging. Conclusion Neuroimaging should be considered in any child with the first episode of unprovoked seizure, especially those with an abnormal neurologic examination or abnormal EEG. Key word: Children; first unprovoked seizure; neuroimaging